2011
DOI: 10.30638/eemj.2011.245
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Analysis of the Integration of Environmental Proactivity Into Managerial Strategy. Identification of Benefits, Difficulties and Facilitators at the Spanish Automotive Industry

Abstract: Industrial firms around the world are focusing on environmental sustainability seeking competitive advantages. Environmental proactivity stands as a fundamental part of these actions. The objective of this work is to understand who and why, companies include the environmental proactivity as an element of the company's strategy. This research has been divided into two separate but interconnected, methodological phases. The first step applied qualitative methods to describe a generic model environmental performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
3
6
0
1
Order By: Relevance
“…This result is in line with previous studies, such as Horbach et al [17], Horbach [51], Triguero et al [58], Cuerva et al [60], and Segarra-Oña et al [106], which argued that technological factors orient eco-innovation. Knowing that information sources are associated with the technology factor, as in Triguero et al [58], and observing the variables used in this study, they are found to have a significant and positive influence on technology, as demonstrated in the study by Lee et al [66], which, based on open innovation, reveals empirically the positive impact of external sources of information on innovation.…”
Section: Discussionsupporting
confidence: 93%
“…This result is in line with previous studies, such as Horbach et al [17], Horbach [51], Triguero et al [58], Cuerva et al [60], and Segarra-Oña et al [106], which argued that technological factors orient eco-innovation. Knowing that information sources are associated with the technology factor, as in Triguero et al [58], and observing the variables used in this study, they are found to have a significant and positive influence on technology, as demonstrated in the study by Lee et al [66], which, based on open innovation, reveals empirically the positive impact of external sources of information on innovation.…”
Section: Discussionsupporting
confidence: 93%
“…In this sense, the chemical industry is often highlighted as one sector which has "the potential to become a driving force to introduce efficient production practices for reducing the negative impact on the environment" (Negny, Belaud, Cortes Robles, Roldan Reyes, & Ferrer, 2012 p. 101). Also the automobile industry is frequently analyzed for its potential regarding product-design and eco-innovation (Sierzchula, Bakker, Maat, & Van Wee, 2012;Segarra-Oña, Carrascosa-López, Segura-García-del-Río, & Peiró-Signes, 2011). However, services have received little attention with regards to eco-innovation in previous literature (Cainelli & Mazzanti, 2013).…”
Section: Meso Level Driversmentioning
confidence: 99%
“…Darnall et al (2008) find empirical evidence in a research performed with industrial companies from Canada, Germany, Hungary and United States, that business value has been created after implementation of environmental management systems. In Spain Segarra et al (2011a) reveal the same profitable relationship in the food industry.…”
Section: Literature Review In Environmental Proactivitymentioning
confidence: 86%
“…The most common way of approaching to environmental proactivity in the existing literature is through quantitative studies based on surveys or interviews (Aragón-Correa, 1998;King & Lenox, 2001;Melnyk et al, 2003;Buysse & Verbeke, 2003;González-Benito & González-Benito, 2005;Dias-Sardinya & Reijnders, 2005;Sharfman, 2008;Aragón-Correa et al, 2008;Darnall et al, 2008;Murillo-Luna et al, 2008;Piñeiro-García et al, 2009;Darnall et al, 2010;Martín-Tapia et al, 2010;Haddock-Fraser & Tourelle, 2010;Delmas et al, 2011;Clarkson et al, 2011;Segarra, 2011a, Lopez-Gamero et al, 2011. Statistical studies confirm the relationship between different factors, but do not explain the origin and the causes of these relationships (González-Benito & González-Benito, 2010).…”
Section: Literature Review In Environmental Proactivitymentioning
confidence: 99%